Implementation of Coastal Coastal Community Empowerment Program Policy in Labean Village, Balaesang District, Donggala District - Darnawati, Darnawati; Nuraisyah, Nuraisyah; Suasa, Suasa (Lafadz Jaya Publisher, 2024)
There are indications of issues in the implementation of the Coastal Community Empowerment Program in Labean Village, Balaesang Subdistrict, facing challenges in evaluating concrete actions by the Social Affairs Office related to preventive, repressive, rehabilitative, and reintegrative efforts. The aim of this research is to analyze the Implementation of the Coastal Community Empowerment Program in Labean Village. This study utilized a qualitative approach with data collection techniques involving interviews, observations, and documentation with stakeholders such as the Social Affairs Office, village heads, community leaders, and related institutions to assess the strategies and evaluations conducted. The research findings show that communication strategies through direct meetings, print media, and social media have been successful in disseminating program information. Collaborations with village heads, community leaders, and a well-organized bureaucratic structure demonstrate strong efforts in supporting the program. However, the evaluation of concrete actions by the Social Affairs Office concerning preventive, repressive, rehabilitative, and reintegrative efforts needs further attention. In conclusion, there is a need for a focus on evaluating concrete actions and improvements in social evaluation strategies to ensure the sustainability and effectiveness of the Coastal Community Empowerment Program in Labean Village.